INTERNALISASI ADAB PESERTA DIDIK DI DALAM KELAS YANG MEMPENGARUHI PROSES PEMBELAJARAN DI MTS GUPPI - Julita, Julita; Hujaj, Jamiatul; Arniyanti, Arniyanti; Anwar HM, Muh (Educational Leadership: Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the dynamics of internalizing students' manners during the learning process in the MTs GUUPPI environment. The research uses a qualitative method with a descriptive approach. Data was collected through in-depth interviews with teachers as well as documentation studies against various relevant written sources, such as books and scientific articles. Data is analyzed qualitatively through the stages of data reduction, data presentation, and systematic conclusion drawn. The results of the study show that the internalization of students' manners is influenced by class level and maturity level. Students in grades VIII and IX showed better manners and learning discipline than students in grade VII who were still in the adaptation stage and had difficulty maintaining concentration in learning. This study concludes that the role and consistency of educators play an important role in shaping students' polite behavior. The implications of this study emphasize the importance of strengthening the role of teachers in fostering adab in a sustainable manner in the school environment.